2019
DOI: 10.46661/ijeri.4045
|View full text |Cite
|
Sign up to set email alerts
|

Effects on academic performance in secondary students according to the use of ICT

Abstract: The main interest of this study was to evaluate the degree of association that the use of ICT could have to school performance in mathematics, within a limited geographical area. The data was obtained thanks to the International Student Assessment Program (PISA). 1376 students from the Canary Islands participated. To obtain the best possible approximation to the phenomenon, a mixed research method was used, in which a linear hierarchical model (HLM) analysis was used to assess the characteristics of students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…It has been shown that ICTs themselves are resources with unlimited potential, and they can be extremely attractive and valuable at the school level. In this sense, coinciding with [ 14 ], we can affirm that the responsible use of ICT positively correlates with the improvement of academic performance in certain subjects. Nevertheless, not all the agents involved in the process are prepared to exploit, rationally and in a beneficial way, the potential of technological resources.…”
Section: Introductionsupporting
confidence: 82%
“…It has been shown that ICTs themselves are resources with unlimited potential, and they can be extremely attractive and valuable at the school level. In this sense, coinciding with [ 14 ], we can affirm that the responsible use of ICT positively correlates with the improvement of academic performance in certain subjects. Nevertheless, not all the agents involved in the process are prepared to exploit, rationally and in a beneficial way, the potential of technological resources.…”
Section: Introductionsupporting
confidence: 82%
“…Thus, we hypothesized that students with better IT skills would perform better academically. Recent literature indicates that successful use of ICT positively affects and improves the performance of students (Díaz and Cano, 2019). Thus, in light of the above evidence, we considered IT skills as a component of this study and hypothesized that if students can utilize essential information technologies, their academic performance would improve.…”
Section: It Skillsmentioning
confidence: 99%
“…Moreover, it maintained the existence of a positive relationship between the ICT resources in the classroom with the students' academic success [19]. Similarly, reference [20] affirmed that inadequate use of technological devices had negative repercussions on learning and on students' academic performance.…”
Section: Discussionmentioning
confidence: 88%
“…The results of recent studies have shown that the availability of ICT resources in schools was positively associated with students' academic success, whereas the availability of ICT resources at home was negatively associated [19]. It has also been observed that inappropriate use of ICT significantly affected students' learning [20]. However, specific software created and developed with attractive and dynamic platforms for students was more effective than general software for teaching and learning [21].…”
Section: The Influence Of Ict On Educational Performancementioning
confidence: 99%